2016
DOI: 10.1002/ece3.2280
|View full text |Cite
|
Sign up to set email alerts
|

Pollen transfer in fragmented plant populations: insight from the pollen loads of pollinators and stigmas in a mass‐flowering species

Abstract: Pollinator and/or mate scarcity affects pollen transfer, with important ecological and evolutionary consequences for plant reproduction. However, the way in which the pollen loads transported by pollinators and deposited on stigmas are affected by pollination context has been little studied. We investigated the impacts of plant mate and visiting insect availabilities on pollen transport and receipt in a mass‐flowering and facultative autogamous shrub (Rhododendron ferrugineum). First, we recorded insect visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
(83 reference statements)
2
16
0
1
Order By: Relevance
“…In patches with low R. ferrugineum density and limited alternative resources, pollinators could compete for less available flower resources (Table 1). Delmas et al (2016) observed more frequent visits to R. ferrugineum and smaller quantities and proportions of its pollen in insect loads in low-density patches than in high-density…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In patches with low R. ferrugineum density and limited alternative resources, pollinators could compete for less available flower resources (Table 1). Delmas et al (2016) observed more frequent visits to R. ferrugineum and smaller quantities and proportions of its pollen in insect loads in low-density patches than in high-density…”
Section: Introductionmentioning
confidence: 84%
“…In patches with low R. ferrugineum density and limited alternative resources, pollinators could compete for less available flower resources (Table ). Delmas et al () observed more frequent visits to R. ferrugineum and smaller quantities and proportions of its pollen in insect loads in low‐density patches than in high‐density patches, suggesting that pollinators had to share fewer resources among more individuals in low‐density patches. We hypothesized that in response to global resource depletion, individuals would either diversify their diet (H2: higher individual generalization) or specialize in different floral resources (H3: higher individual specialization) with different consequences for individual and species networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Floral constancy, or fidelity, refers to when a pollinator consistently prefers one plant species to another; the less preferred species may experience reduced fitness (Campbell and Motten 1985). Pollinators often exhibit more constancy (Kunin 1997) and carry more conspecific pollen (Delmas et al 2016) in high-density populations. Consequently, we might expect that generalist pollinators exhibit the highest fidelity to a plant species during peak flowering of that species, when conspecific plant density is highest.…”
Section: Introductionmentioning
confidence: 99%
“…More attractive patches are predicted to receive a greater quantity of pollen by optimal foraging theory, and as a result, more pollen deposition yields a positive correlation between individual patch size with fecundity and seed viability (Jennersten and Nilsson, 1993). Similar principles can also be applied at a population scale as well; optimal foraging theory predicts that groups of large patches will be favored and that small neighboring patches may also prosper from local pollinator activity (Delmas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%